Persoalan riba dalam aktifitas pelepas modal: tinjauan humanisme dan moralitas agama - Zulfa, M (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2012)
This article presents a preliminary study on cases of interests added loans between the creditors and small scale merchants. The cases are seen through the textual perspective as the interests embedded transactions (riba). Thus, textually, these kinds of transactions are said to have violated or at least ignored the religious law (fiqh). But in reality, these practices exist and continuous to exist. Hence, there is a thought whether the interconnected and interdisciplinary approach aimed at promoting the spirit of humanity and religious morality can accommodate these practices. This is due to the argument that the religious teaching based merely on texts may provoke exclusivist attitudes that will be less conducive for todayâs cultural and religious globalization era. However, the contextual approach neglecting the textual norms as guidance and directions for everydayâs lives will trap someone into the nihilistic attitudes. One of the characteristics of the philosophical approach -in the era of post-existentialism- toward multi faces of Islam is the pattern of the study which does not merely refer to texts of the holy Book and the Prophetâs traditions literally, out of contexts.